Analysis Of Factors Affecting Credit Access And Their Impact On Welfare - Asfi Manzilati; Yenny Kornitasari; Suprayogi Suprayogi; Anthon Efani (Journal of International Conference Proceedings, 2022)
This study aims to analyze the factors that influence access to credit and analyze the impact of access to credit on welfare. So far, a number of important international studies to access credit services that are considered capable of reducing poverty in low-income communities. Credit in the fisheries sector is able to provide input for fishermen to carry out fishing activities. the availability of credit makes fishermen more eligible to increase their productivity, so it is natural when credit request services are needed to improve the welfare of the fishing community. Data was collected by surveying small fishermen in Malang and Probolinggo districts using a questionnaire. Furthermore, the data will be analyzed with descriptive statistical tests, and Instrumental Variable (IV) logit, and Endogenous Switching Regression. The results showed that the variables that had no significant effect on fishermen's credit access were experience and ship size. Meanwhile, the variables of age, education, and fisherman group have a significant influence on fishermen's credit access. The impact on welfare shows that households that have access to formal credit have higher incomes by 33.8% to 44.4% compared to households that do not have access to formal credit. The implication of research is that with access to credit, the welfare level of fishermen will increase.Â Keywords: Credits; Well-being; small fisherman; endogenous transiti